(untitled) (REMUNOM, 2025)
The arrival of a new family member is a period of change that brings anticipation, fear, and insecurity. It is a time that can trigger a delicate mental health condition in the mother. Postpartum depression (PPD) is a condition that manifests subtly and has a significant impact not only on the mother but also on the newborn and the family unit. Early diagnosis and treatment are of utmost importance during this period. Therefore, the aim is to investigate the role of nurses in the prevention, early detection, and intervention in the context of postpartum depression. For this purpose, a literature review was conducted. It was observed that nurses are fundamental at all stages of care, from prenatal to postpartum, demonstrating great skill in building bonds with pregnant women and mothers, offering a welcoming and trustworthy environment.